Case Report: Management of cerebral arterial gas embolism via transfer to an outpatient hyperbaric chamber - Emmanuel J. Thomas; Samuel J. Thomas; Jason A. Bailey; Jason A. Bailey; Jason M. Jaronik; Hassaan A. Khan; Manaal Buchh; Zenia Qasim; Saniya K. Zackariya; David E. Van Ryn; David E. Van Ryn; David E. Van Ryn; et al. (Frontiers in Medicine)
Gas embolisms can be caused by iatrogenic interventions, resulting in various manifestations. We present a patient who experienced loss of consciousness and simultaneous paralysis during a percutaneous needle biopsy of the lung. A CT scan of the head revealed a cerebral arterial gas embolism. Because the treating hospital did not have access to hyperbaric oxygen for immediate treatment, the patient was transferred to an outpatient wound care facility. There, the patient initially improved when treated with hyperbaric oxygen therapy but deteriorated with resumption of ambient pressure. Continued treatment occurred at another hospital where the patient’s condition normalized. The initial transfer of the patient to another facility was notable because it was a transfer from a rural hospital, a higher-level facility, to an offsite wound care center with a hyperbaric chamber, a lower-level facility that could provide a higher level of care. This case report demonstrates the importance of immediate treatment of iatrogenic gas embolism with hyperbaric oxygen, which often is not available at many hospitals, and highlights the necessity to adapt to the transport of the patient from a higher-level facility to a lower-level facility when such transportation is necessary to provide effective and immediate care. This report is not recommending routinely transferring such patients to a lower level of care facility. However, when deemed clinically necessary and safe by bedside emergency physicians/critical care pulmonary physicians, it is a viable option. Explicit guidelines for transfers to lower-level facilities should be established to avoid delays in these situations.